2018
DOI: 10.1103/physrevd.98.063007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating radiation transport errors in merger simulations using a Monte Carlo algorithm

Abstract: Neutrino-matter interactions play an important role in the postmerger evolution of neutron star-neutron star and black hole-neutron star mergers. Most notably, they determine the properties of the bright optical/ infrared transients observable after a merger. Unfortunately, Boltzmann's equations of radiation transport remain too costly to be evolved directly in merger simulations. Simulations rely instead on approximate transport algorithms with unquantified modeling errors. In this paper, we use for the first… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 66 publications
2
69
0
Order By: Relevance
“…In the M1 scheme, the moments representation of the Boltzmann equation is truncated at the second moment and a closure interpolating between the thin and thick regime is imposed to the equations. The compact binaries simulations performed so far with this scheme are performed in the gray regime [122,214,279]. The leakage scheme is an approximation to the transport problem that accounts for changes to the lepton number and for the loss of energy due to the emission of neutrinos.…”
Section: A Appendix A: Numerical-relativity Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the M1 scheme, the moments representation of the Boltzmann equation is truncated at the second moment and a closure interpolating between the thin and thick regime is imposed to the equations. The compact binaries simulations performed so far with this scheme are performed in the gray regime [122,214,279]. The leakage scheme is an approximation to the transport problem that accounts for changes to the lepton number and for the loss of energy due to the emission of neutrinos.…”
Section: A Appendix A: Numerical-relativity Methodsmentioning
confidence: 99%
“…The neutrino wind originates on the disc edge, close to the neutrinosphere, and above the remnant where baryon pollution is minimal. Note that a precise prediction of properties of polar ejecta is presently beyond the possibilities of neutrinos schemes employed in ab-initio NR simulations [43,45,184,214].…”
Section: Mass Ejectamentioning
confidence: 99%
“…In all simulations, a small amount of cold, neutron-rich material is dynamically ejected in the equatorial plane by the merger: 0.002 M ⊙ (0.004 M ⊙ ) for NS-NS and <0.001 M ⊙ for NS-BH binaries. Less neutron-rich polar ejecta is observed, but in the absence of magnetic fields its mass is negligible (and not resolved in the simulations); see [44]. Note that none of our simulations produce a relativistic jet, e.g., as observed for GW170817 [45,46], which is unsurprising as our simulations do not include any magnetohydrodynamics (MHD) effects (see [47] for incipient jets in a NS-BH simulation).…”
Section: Numerical-relativity Simulationsmentioning
confidence: 82%
“…ILEAS is not only computationally very efficient but also appears to be competitive concerning its accuracy compared to other forefront developments of neutrino transport treatments for CO mergers and their remnants. The work by Foucart et al (2018) underlines that M1 solutions have their own shortcomings when applied to the highly aspherical environments of merger remnants. For this reason our tests with BH-torus systems, comparing ILEAS to M1 results from the ALCAR code, cannot be considered as finally conclusive regarding the accuracy of ILEAS.…”
Section: Discussionmentioning
confidence: 99%
“…We refrain from performing a comparison of the rates immediately above the BH and in the close vicinity of the z-axis, because a consistent treatment of general relativistic and special relativistic effects would be needed to describe the influence of the BH or ultrarelativistic GRB jets. Furthermore, Foucart et al (2018), for example, compared Monte Carlo results and M1 results in the context of a HMNS surrounded by a torus and pointed out that the inexact M1 closure strongly overestimates the number density in the polar regions, by ∼50 per cent for νe andνe, which leads to significant boosting of the absorption rates by charged-current reactions and excess heating. Just et al (2015a) also reported similar behaviour when comparing BH-torus calculations with a ray-tracing Boltzmann solver against their M1 results.…”
Section: Snapshot Calculations: Black Hole-torus Systemmentioning
confidence: 99%